STRATEGI PENYELESAIAN KONFLIK DALAM KELUARGA DI MASA PANDEMI COVID-19 - Anggi Yus Susilowati; Andi Susanto (Hasanuddin Journal of Sociology, 2020)
The purpose of this research is to study the appropriate conflict resolution strategies in resolving family conflictsduring the pandemic. The research method used in this research is library research method. The results of the studyshow that conflicts within the family during the pandemic, when viewed from the conflicting parties, include conflictbetween husband and wife, conflict between parents and children, and conflict between siblings. The cause of the familyconflict is due to two factors, namely originating from personality problems and other family problems such as familyfinances or economics, household chores, childcare problems, and interaction problems within the family. Family conflictresolution strategies can be carried out in two methods, namely self-resolving conflict resolution using severalapproaches that can be used such as collaboration or compromise approaches, defeating opponents or competitions,and avoiding. Conflict resolution methods in resolving family conflicts can also be done with third party interventions to helpresolve conflicts that occur. Abstrak Tujuan dari penelitian ini yakni untuk mengkaji strategi penyelesaian konflik yang tepat dalam menyelesaikan konflikkeluarga dimasa pandemi. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kepustakaan.Hasil dari penelitian menunjukan bahwa konflik di dalam keluarga pada masa pandemi jika dilihat dari pihak yangberkonflik meliputi konflik pasangan suami istri, konflik antara orang tua dan anak, serta konflik antarsaudara. Penyebabterjadinya Konflik keluarga tersebut dikarenakan atas dua faktor yakni bersumber dari masalah kepribadian danbersumber dari masalah keluarga lainnya seperti keuangan atau ekonomi keluarga, masalah pekerjaan rumah tangga, masalah pengasuhan anak, serta masalah interaksi di dalam keluarga. Strategi penyelesaian konflik keluarga dapat dilakukan dengandua metode yakni resolusi konflik penyelesaian sendiri dengan menggunakan beberapa pendekatan yang dapat digunakan seperti pendekatan kolaborasi atau kompromi, mengalahkan lawan atau kompetisi, serta menghindar. Metode resolusi konflik dalam penyelesaian konflik keluarga juga dapat dilakukan dengan intervensi pihak ketiga untuk membantu menyelesaikan konflik yang terjadi